2015
DOI: 10.1038/nature14066
|View full text |Cite
|
Sign up to set email alerts
|

Distinct relationships of parietal and prefrontal cortices to evidence accumulation

Abstract: Gradual accumulation of evidence is thought to be fundamental for decision-making, and its neural correlates have been found in multiple brain regions1–8. Here we develop a generalizable method to measure tuning curves that specify the relationship between neural responses and mentally-accumulated evidence, and apply it to distinguish the encoding of decision variables in posterior parietal cortex (PPC) and prefrontal cortex (frontal orienting fields, FOF). We recorded the firing rates of neurons in PPC and FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
621
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(726 citation statements)
references
References 29 publications
56
621
8
Order By: Relevance
“…2). Previous optogenetic inactivation studies focusing on related brain areas have interpreted a lack of effect of transient inactivation as a lack of role in behavior 13,42 . Our results imply that redundancy across a distributed network could mask possible causal roles in optogenetics experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Previous optogenetic inactivation studies focusing on related brain areas have interpreted a lack of effect of transient inactivation as a lack of role in behavior 13,42 . Our results imply that redundancy across a distributed network could mask possible causal roles in optogenetics experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in frontal and parietal cortex show slow dynamics, including persistent and ramping activity, related to motor planning [1][2][3][4] , action timing 5,6 , working memory [7][8][9][10] and decision making [11][12][13] . Neurons have intrinsic time constants on the order often milliseconds 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Behaviorally, M2 has been implicated in top–down modulation of somatosensory based orienting and appetitive approach behaviors (Erlich et al, 2011; Guo et al, 2014). Additionally, M2 projects to parietal regions (MPtA, LPtA), which are involved in evidence accumulation and decision formation (Hanks et al, 2015). M2 neurons encode a categorical classification of evidence in decision making, while parietal neurons encode a more continuous representation of accumulated evidence (Hanks et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of perceptual decisions in primates (Kira, Yang, & Shadlen, 2015;Yang & Shadlen, 2007) and in rodents (Hanks et al, 2015) showed that the firing rates of neurons in the parietal cortex reflected the gradual accumulation of logLR when different logLRs were assigned to various sensory cues. Although the underlying neural mechanisms are less understood, a similar framework explains a variety of P3b-like phenomena that are related to perceptual decisions in humans (Kelly & O'Connell, 2013;O'Connell, Dockree, & Kelly, 2012).…”
Section: The P3b Component In the Urn-ball Taskmentioning
confidence: 99%